Bizarre parosteal osteochondromatous proliferation (Nora's lesion) of phalanx in a child. (23rd January 2014) - Kumar, Ashok; Khan, Shah Alam; Sampath Kumar, Venkatesan; Sharma, Mehar Chand
Abstract : Bizarre parosteal osteochondromatous proliferation (BPOP; also called Nora's lesion) is a benign surface osteocartilaginous lesion, which is infrequently reported in world literature. The condition is classically described in the short tubular bones of hands and feet in the second and third decades of life. We present a case report of BPOP of the middle phalanx of middle finger in a 4-year-old girl. The child underwent a wide excision and remained asymptomatic at 2.5 years of follow-up. Our case report highlights the importance of suspecting Nora's lesion in a child. It also helps in delineating a differential diagnosis and discusses the management principles of this rare osteocartilaginous lesion.